Analisis Pengaruh Pertumbuhan Ekonomi, Pertumbuhan Penduduk Dan Inflasi Terhadap Tingkat Pengangguran Di Provinsi Sumatera Barat - Putri Selviana Anjani; Rika Marlina; Vicky F. Sanjaya (KALIANDA HALOK GAGAS, 2023)
Abstrak This study aims to determine whether or not good socio-economically indicators affecting unemployment in West Sumatra Province. This study uses secondary data from the official BPS website from 2012 to 2022 and also sources from journals, articles and government agencies, such as Indonesian Statistics. The data analysis technique uses panel data regression analysis. The findings show that population growth has a positive and significant effect on unemployment in West Sumatra Province. Population growth does not necessarily reduce the unemployment rate in West Sumatra Province. economic growth has a negative and significant effect on unemployment in Sumatra Province; every upgrade in Economic growth can reduce the unemployment rate in West Sumatra Province. Inflation has a positive and insignificant effect on unemployment in West Sumatra Province; but inflation does not necessarily reduce the unemployment rate in West Sumatra Province. Keywords: : Economic Growth, Population Growth, Inflation, Unemployment Rate ABSTRAK : Penelitian ini bertujuan untuk mengetahui baik tidaknya secara sosial ekonomi indikator yang mempengaruhi pengangguran di Provinsi Sumatera Barat. Penelitian ini menggunakan data sekunder dari website resmi BPS tahun 2012 hingga 2022 dan juga sumber dari jurnal, artikel dan instansi pemerintah seperti Statistik Indonesia. Teknik analisis data menggunakan analisis regresi data panel. Hasil penelitian menunjukkan bahwa pertumbuhan penduduk berpengaruh positif dan signifikan terhadap pengangguran di Provinsi Sumatera Barat. Populasi pertumbuhan tidak serta merta mengurangi tingkat pengangguran di Provinsi Sumatera Barat. pertumbuhan ekonomi berpengaruh negatif dan signifikan terhadap pengangguran di Provinsi Sumatera; setiap peningkatan di Pertumbuhan ekonomi dapat mengurangi tingkat pengangguran di Provinsi Sumatera Barat. Inflasi berpengaruh positif dan tidak signifikan terhadap pengangguran di Provinsi Sumatera Barat; tetapi inflasi tidak serta merta mengurangi tingkat pengangguran di Provinsi Sumatera Barat. Kata kunci : Pertumbuhan Ekonomi,Pertumbuhan penduduk,Inflasi,Tingkat Pengangguran